Tribological properties of wax microcapsule modified polymers - Ang, Ping Lon (2013)
Epoxy resins have great mechanical properties and they can be formed with many different types of epoxy and hardeners to achieve desired properties. Research showed that adding fillers into the epoxy matrix helped to reduce friction coefficient and wear. One type of fillers used is oil-based lubricants. In this project, the lubricant used is microencapsulated wax, EPIWAX B33, a typed of paraffin wax, which is mix within the epoxy matrix. A total of 6 epoxy composites with different wax microcapsules concentration were tested- 0, 0.5, 1.5, 3.5 and 7%wt. Surface roughness and micro indentations were first done to determine the initial surface conditions, before putting the epoxy samples through tribological test to determine friction coefficient and wear. The tribology test uses the Pin-On-Disk wear test method and the default tribometer settings used in this project were set at 2000m sliding distance, 40cm/s linear speed and 3N linear load. After which the wear on the surface is further analyzed using Talyscan 150 to measure wear width and wear depth to understand the lubricating effects of the addition of wax microcapsules. The SEM images of the surfaces are obtained to analyze the morphology of the surfaces after going through tribological testings. It was found that the addition of wax microcapsules significantly reduces the friction coefficient and wear, but there is a cut-off point to this attribute. After this cut-off point, further increase of wax microcapsules increases the friction coefficient and wear. The hardness and modulus properties of epoxy composites decrease with the increase of wax microcapsules concentration. From the results obtained in the project, the right balance can be obtained at 3%wt, which does not compromise the physical properties of the epoxy and at the same time, giving the lowest friction coefficient and wear.